BILATERAL COMPARATIVE ADVANTAGES: INDONESIA AND MALAYSIA CASE - Ni Putu Wiwin Setyari (MediaTrend, 2015)
This study tried to look more closely at market integration, through export prices channel, in Indonesia and Malaysia. Several previous studies tend to reject the existence of law of one price (LOP). The law of one price (LOP) states that price a given product should be the same in different parts of the world if valued in common currency. However, empirical studies uniformly shows LOP does not describe most markets. Some important factors that are considered instrumental in this regard are transportation costs and price stickiness. However, there is one characteristic that is often overlooked in the discussion of LOP, namely changes in comparative advantage. The specific objective of this paper is to look at comparative advantage correlation between the two countries and their effect on price convergence. Correlation of both selected commodities – using the rank spearman's test - indicates the nature of the mutual substitution of products that carry the possibility of "price competition" so that the price point to converge to one another. Tests on the export price of some selected products in both countries indicated the occurrence of price convergence, seen from the two analytical techniques: σ convergence and co-integration using Johansen's test. This conclusion is generated by attempted to control the "identical assumption" is to examines prices for similar products (homogeneous) using SITC 3-digit, which is produced from the "same" or close locations, with the export destination to the same trading partner